Below the surface : African learners' experiences of schooling in a predominantly Indian school in KwaZulu-Natal. - Pillay, Thanjamah. (2010)
This research explores the experiences of African learners in a school in which they constitute the minority. The aim of the study is to investigate how African learners perceive of their day to day experiences in an ex-House of Delegates school that still has a predominantly Indian learner population. The study was conducted in a primary school situated in a small suburb south of Durban. Ten African learners from grade seven were interviewed through semi-structured interviews in this qualitative study. This was followed by a focus group discussion with the ten respondents to further investigate specific issues and to serve as a debriefing since strong emotions had surfaced. Interviews were recorded on audiotape, and non-verbal indicators were recorded in the form of written notes. Non-participant observations were also conducted on the playgrounds. The content analysis method was used to analyze the data. Themes were identified and related to the conceptual framework of the study. The analysis revealed that learners experienced various exclusionary pressures as African learners in a predominantly Indian school. Unequal power relations are perpetuated through the intersection of race, class and ability as well as through a hidden curriculum. Racism as a form of oppression was evident in the racist name-calling and racist stereotyping. There appears to be a lack of a caring pedagogy as African learners feel marginalized. The findings reveal the need for a whole-school policy on anti-racist education. In addition, educators need training to help them interrogate the cycle of socialization to which they have been exposed. The implications are specific to the context. The formulation of a whole-school policy on anti-racist education and an educator intervention program are some of the recommendations. === Thesis (M.Ed.)-University of KwaZulu-Natal, Durban, 2004.